Improving the Academic Achievement of Engineering Undergraduates Through the Intervention of Biofeedback Training Protocol - Mohd Ghani, Awang; Muhammad Nubli, Abdul Wahab; Suriya Kumar, Sinnadurai; Roshasliza, Samat (Penerbit Universiti Malaysia Pahang, 2009)
Poor academic performance among undergraduates can be associated with many factors. Among them are poor concentration, poor personality performance and peer influence. These are considered the most significant factors that lead to poor academic achievement among students. This study is proposing a new method to improve student's academic performance. It employs personality profiling information system together with a biofeedback game protocol. The model uses computer based personality profiling to explore personality problems among students. It also uses biofeedback devices that can detect emotional performance of the user. Participants with a low academic achievement were selected randomly as a sample for the research. They are given a training module and have to attend a few biofeedback training sessions. They are also required to correct their misbehaviour based on the module given to them. During biofeedback training session, they are required to improve their emotional performance and practice the protocol on a daily basis. After completing the training, the result shows that the participants are able to improve their academic performance. They can increase Cumulative Point Average (CPA) results from being in the low achiever category to high achievers. The results of the study shows that the proposed module and the biofeedback training protocol are able to assist engineering undergraduates in improving their academic performance.